Wear Analysis of Tooth Surface of Rack-and-pinion with Variable Mounting Distance for Rack Railway - Yingjie Xu; Peng Zheng; Yunfeng Liu; Yang Gao; Wenbo Xu (Jixie chuandong)
As rack-and-pinion is the key driving part of rack railway， mastering the wear condition and law of the gear rack pair tooth surface during the operation of the gear rail vehicle is conducive to ensuring the smooth and safe operation of the gear rail vehicle. For this purpose， the process of variable mounting distance transmission of rack-and-pinion in the form of Strub rack railway is analyzed， and the key parameters of variable mounting distance transmission are calculated accordingly； by introducing the mounting distance step and slip distance step， the continuous transmission process of rack and pinion pair with variable mounting distance is discretized， and the mathematical model of wear volume and wear depth of tooth surface of variable installation distance rack-and-pinion is constructed； in order to verify the accuracy of the mathematical model， rack wear test is carried out； combined with concrete examples， the influence of different parameters on tooth surface wear is analyzed to obtain the key factors affecting the wear of tooth surface and their influencing rules. The results show that the measured value of tooth surface wear depth is consistent with the theoretical value of the model， which verifies the accuracy of the model. As the wear at the top of the rack teeth is the most serious， choosing the gear with larger displacement coefficient is conducive to reducing the wear of the rack tooth surface.